Aluminum fin material and method for manufacturing same
By adding silicone containing epoxy groups to the corrosion-resistant film layer of aluminum fins, the manufacturing cost problem caused by the large amount of film in the prior art is solved, and efficient corrosion resistance and good heat exchange are achieved. performance.
Patent Information
- Application Number
- CN202411021105.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-04
- Filing Date
- 2024-07-29
- Publication Date
- 2025-02-14
AI Technical Summary
When the prior art suppresses corrosion of aluminum plates, it is difficult to achieve equal or more corrosion resistance with a smaller amount of film, resulting in an increase in manufacturing costs.
In addition to the epoxy resin, silicone containing epoxy groups is added to form a corrosion-resistant film layer with high homogeneity in addition to the epoxy resin to form a corrosion-resistant film layer.
Very excellent corrosion resistance is achieved, and sufficient corrosion resistance can be maintained even if the amount of the film is reduced, thereby reducing the manufacturing cost and not affecting the thermal conductivity and heat exchange efficiency of the aluminum fins.
Smart Images

Figure BDA0004967288750000171 
Figure BDA0004967288750000181
Abstract
Description
Technical Field
[0001] The invention relates to an aluminum fin material and a manufacturing method thereof. Background Art
[0002] Heat exchangers are used in products in various fields such as room air conditioners, modular air conditioners, refrigerated display cabinets, refrigerators, oil coolers, radiators, etc. The material of the fins of the heat exchanger is generally aluminum or aluminum alloys with excellent thermal conductivity, processability, corrosion resistance, etc. Plate fin type or plate and tube type heat exchangers have a structure in which fins are arranged in parallel at narrow intervals.
[0003] When the cooling equipment is running, the aluminum fin material of the heat exchanger has a cooled refrigerant flowing in the copper tube, and the surface temperature of the fin material is lower than the dew point. As a result, condensation water adheres to the surface of the fin material. Due to the influence of the condensation water, the surface of the aluminum fin material is easily corroded.
[0004] The aluminum corrosion products generated by the above corrosion may not only serve as attachment points for odor components in the atmosphere, but may also cause various problems such as splashing due to surface water repellency caused by the attachment of water repellent components, and the odor of the corrosion products themselves.
[0005] In this regard, Patent Documents 1 to 3 propose a technique of coating a water-repellent corrosion-resistant film layer on the surface of an aluminum plate in order to suppress corrosion. Specifically, Patent Documents 1 to 3 disclose a structure in which a corrosion-resistant film containing a hydrophobic resin is provided between an aluminum plate and a hydrophilic film.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2021-162164
[0009] Patent Document 2: Japanese Patent Application Publication No. 2021-162165
[0010] Patent Document 3: Japanese Patent Application Publication No. 2022-161706 Summary of the invention
[0011] Problems to be solved by the invention
[0012] Although the corrosion of the aluminum plate can be suppressed by providing a corrosion-resistant film layer, achieving equal or higher corrosion resistance with a smaller film amount leads to a reduction in manufacturing cost, etc. Therefore, a corrosion-resistant film layer with higher corrosion resistance is desired.
[0013] Therefore, an object of the present invention is to provide an aluminum fin material having extremely excellent corrosion resistance and a method for producing the same.
[0014] Means of solving the problem
[0015] The present inventors studied the above problems and found that by including epoxy-containing silicone in the corrosion-resistant film layer in addition to the conventional epoxy resin, extremely excellent corrosion resistance can be achieved, thereby completing the present invention.
[0016] The present invention relates to the following [1] to [8].
[0017] [1] An aluminum fin material comprising, in order, an aluminum plate, and a corrosion-resistant film layer and a hydrophilic film layer on at least one surface of the aluminum plate,
[0018] The corrosion-resistant film layer includes an epoxy resin and silicone containing an epoxy group.
[0019] [2] The aluminum fin material according to [1] above, wherein the content of the epoxy-containing silicone in the corrosion-resistant film layer is 0.1 to 20% by mass.
[0020] [3] The aluminum fin material according to [1] or [2], wherein the amount of the corrosion-resistant film layer is 0.1 to 20 mg / dm 2 .
[0021] [4] The aluminum fin material according to any one of [1] to [3] above, wherein the hydrophilic film layer includes an acrylic resin containing a sulfonic acid group and an ether bond.
[0022] [5] The aluminum fin material according to any one of [1] to [4], further comprising a lubricating film layer on the surface of the hydrophilic film layer.
[0023] [6] The aluminum fin material according to [5] above, wherein the lubricating film layer comprises: a resin matrix containing polyethylene glycol as a main component; and a hydrophilic component containing at least one of a sulfonic acid group and an ester group.
[0024] [7] The aluminum fin material according to any one of [1] to [6], further comprising a surface treatment layer between the aluminum plate and the corrosion-resistant film layer.
[0025] [8] A method for manufacturing an aluminum fin material, the aluminum fin material comprising an aluminum plate, and a corrosion-resistant film layer and a hydrophilic film layer on at least one surface of the aluminum plate in order, wherein the method comprises a step of applying and dehydrating a coating composition comprising an epoxy resin composition and at least one of silicon having an epoxy group and a silane coupling agent to form the corrosion-resistant film layer.
[0026] Effects of the Invention
[0027] The aluminum fin material of the present invention has extremely excellent corrosion resistance. Therefore, even if the amount of the corrosion-resistant film layer is smaller than before, sufficient corrosion resistance can be achieved. As a result, the manufacturing cost can be reduced.
[0028] In addition to the above, when aluminum fin materials are used in heat exchangers such as air conditioners, the amount of the corrosion-resistant film layer can be reduced, that is, the layer thickness can be thinned, so it is possible to provide an aluminum fin material that does not hinder the thermal conductivity and heat exchange efficiency required of the aluminum fin material, while also having excellent corrosion resistance. DETAILED DESCRIPTION
[0029] Hereinafter, the embodiment of the aluminum fin material of the present invention will be described in detail. In addition, the term "to" indicating a numerical range is used to mean that the numerical values before and after the range are included as the lower limit and the upper limit.
[0030] 《Aluminum fin material》
[0031] The aluminum fin material (hereinafter simply referred to as “fin material”) of the present embodiment includes an aluminum plate, and a corrosion-resistant film layer and a hydrophilic film layer on at least one surface of the aluminum plate in this order.
[0032] 〈Corrosion-resistant film layer〉
[0033] The corrosion-resistant film layer of the present embodiment includes an epoxy-based resin and epoxy-group-containing silicone.
[0034] The fin material of this embodiment includes the corrosion resistant film layer between the aluminum plate and the hydrophilic film layer. When the fin material further includes a base treatment layer, the corrosion resistant film layer is preferably provided between the base treatment layer and the hydrophilic film layer.
[0035] The corrosion-resistant film layer is a layer for improving the corrosion resistance of the aluminum plate, and blocks the intrusion of moisture such as condensed water, oxygen, ions such as chloride ions, etc. into the aluminum plate. As a result, the corrosion of the aluminum plate and the generation of aluminum oxides that cause odor are suppressed.
[0036] In addition, the corrosion-resistant film layer can also improve the adhesion between the aluminum plate and the hydrophilic film layer, making the function of the hydrophilic film layer more durable. As a result, in addition to the corrosion-resistant function, the corrosion-resistant film layer can also improve the film-forming property, the heat exchange efficiency of the fin material, and the hydrophilic function of the hydrophilic film layer.
[0037] In accordance with the effect of the above-mentioned corrosion-resistant film layer, the corrosion-resistant film layer of the present embodiment includes silicone containing epoxy groups in addition to the epoxy resin, thereby achieving extremely excellent corrosion resistance.
[0038] The reason for this has not yet been determined, but the following considerations are possible.
[0039] First, epoxy-containing silicone is a polymer compound obtained by polymerizing a silane compound having a main skeleton formed by siloxane bonds into which epoxy groups are introduced, and can be obtained, for example, by dehydration condensation of silicon having epoxy groups or a silane coupling agent having epoxy groups.
[0040] Since silicon and the silane coupling agent, which can be regarded as precursors of silicone, have epoxy groups, the compatibility of the epoxy resin with silicon and the silane coupling agent is improved, and as a result, it is presumed that a highly homogeneous corrosion-resistant film layer can be obtained.
[0041] High homogeneity means that the epoxy resin and silicone will not separate and there is no clear interface between the two. The high homogeneity of the corrosion-resistant film layer is used to inhibit moisture and ion species that are the cause of aluminum plate corrosion from passing through the corrosion-resistant film layer and reaching the aluminum plate, and as a result, it is believed that very excellent corrosion resistance can be achieved.
[0042] The main skeleton formed of siloxane bonds of the epoxy-containing silicone may be a linear siloxane skeleton or a cyclic siloxane skeleton, but a linear siloxane skeleton is preferred from the viewpoint of ensuring uniform dispersibility in the coating material.
[0043] Specific examples of silicon having an epoxy group include KF series manufactured by Shin-Etsu Silicone Co., Ltd. and DOWSIL manufactured by Dow Toray Industries, Inc.
[0044] Specific examples of the silane coupling agent having an epoxy group include, for example, KBM series manufactured by Shin-Etsu Silicone Co., Ltd. and DOWSIL manufactured by Dow Toray Industries, Inc.
[0045] The content of silicone having an epoxy group in the corrosion-resistant film layer of the present embodiment is preferably 0.1 to 20% by mass. Here, from the viewpoint of corrosion resistance, the above content is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and further preferably 0.5% by mass or more. In addition, from the viewpoint of hydrophilicity, the above content is preferably 20% by mass or less, more preferably 10% by mass or less, and further preferably 5% by mass or less.
[0046] The epoxy resin in the present embodiment is a resin obtained by crosslinking and curing epoxy groups remaining in a polymer.
[0047] As prepolymers before curing of epoxy resins, for example, bisphenol A type, bisphenol F type, bisphenol S type, or halogen, alkyl substitution, hydrogenation products of these bisphenols, etc. In addition, as curing agents, polyamines, acid anhydrides, polyamides, imidazoles, etc. can be listed.
[0048] Commercially available products of bisphenol A-type epoxy resins include, for example, jER (registered trademark) 1001, 1002, 1003, 1004, 1004AF, 1005, 1006FS, 1007, 1009, and 1010 manufactured by Japan Epoxy Resin Co., Ltd., EPOTO (registered trademark) YD-011, YD-012, YD-013, YD-014, YD-017, YD-019, and YD-020G manufactured by Tohto Chemical Co., Ltd., and EPICLON (registered trademark) 860, 1050, 1055, 3050, 4050, and 7050 manufactured by DIC Corporation.
[0049] Examples of commercially available brominated bisphenol A epoxy resins include jER (registered trademark) 5046B80, 5047B75, 5050, 5050T60, and 5051 manufactured by Japan Epoxy Resins Co., Ltd. and EPICLON (registered trademark) 152 and 153 manufactured by DIC Corporation.
[0050] Examples of commercially available products of bisphenol F-type epoxy resins include jER (registered trademark) 806, 807, 4002P, 4004P, 4007P, and 4009P manufactured by Japan Epoxy Resins Co., Ltd. and EPOTO (registered trademark) YDF-2001 and YDF-2004 manufactured by Tohto Kasei Co., Ltd.
[0051] As a commercial product of a bisphenol S type epoxy resin, EPICLON (registered trademark) EXA-1514 manufactured by DIC Corporation etc. are mentioned, for example.
[0052] The content of the epoxy resin in the corrosion-resistant film layer in the present embodiment is preferably 80 to 99.9% by mass. From the viewpoint of hydrophilicity, the content is preferably 80% by mass or more, more preferably 90% by mass or more, and further preferably 95% by mass or more. From the viewpoint of corrosion resistance, the content is preferably 99.9% by mass or less, more preferably 99.8% by mass or less, and further preferably 99.5% by mass or less.
[0053] The corrosion-resistant film layer of the present embodiment may also contain other resins other than epoxy resins. Other resins are preferably hydrophobic resins, for example, polyolefin resins, acrylic resins, polyester resins, polyurethane resins, melamine resins, etc. These other resins may contain one or more. The above other resins are preferably water-dispersible.
[0054] When the above-mentioned other resins are contained, polyolefin-based resins and acrylic resins are preferred. The acrylic resin may be any of acrylic resins and polyacrylates, but acrylic resins are more preferred.
[0055] As polyolefin resins, polyethylene, polypropylene, etc. can be cited, and these are preferred from the viewpoint of making the corrosion-resistant film layer soft and reducing defects such as cracks. In addition, acrylic resins are preferred because they form interactions such as hydrogen bonds and crosslinks between the hydrophilic film layer, further improving the adhesion between the films.
[0056] The epoxy resin and other resins in this embodiment may be in a chain form or may be cross-linked.
[0057] In the case of crosslinking, for example, acrylic resin can be crosslinked by dehydration condensation caused by baking during film formation, etc. Crosslinking by dehydration condensation can also be formed via polyols such as carboxymethyl cellulose, polyvinyl alcohol, polyethylene oxide, etc.
[0058] In addition, in the case of cross-linking, cross-linking may be performed using a cross-linking agent.
[0059] Examples of the crosslinking agent include isocyanate crosslinking agents, epoxy crosslinking agents, oxazoline crosslinking agents, carbodiimide crosslinking agents, and aziridine crosslinking agents.
[0060] The corrosion-resistant film layer of the present embodiment may contain other optional components in addition to the above, within the range not impairing the effects of the present invention. Examples of the optional components include various coating additives for improving the physical properties of the film.
[0061] As coating additives, for example, crosslinking agents, surfactants, surface conditioning agents, wetting and dispersing agents, anti-precipitation agents, antioxidants, defoamers, rust inhibitors, antibacterial agents, etc. can be listed. Among them, it is preferred to contain an antibacterial agent. These coating additives can also include one or more.
[0062] The amount of the corrosion-resistant film layer is preferably 0.1 to 20 mg / dm 2 Here, from the viewpoint of good corrosion resistance and inter-layer adhesion, the above-mentioned film amount is preferably 0.1 mg / dm 2 More preferably 1.0 mg / dm 2 More preferably, 1.5 mg / dm 2 On the other hand, in addition to the viewpoint of good film forming properties and reduction of defects such as cracks, the above-mentioned film amount is preferably 20 mg / dm from the viewpoint of suppressing the thermal resistance of the film to be low, suppressing the hindrance of the heat exchange efficiency of the fin material, and not hindering the functions of other film layers. 2 Below, more preferably 18 mg / dm 2 Below, more preferably 15 mg / dm 2 the following.
[0063] The amount of the corrosion-resistant film layer can be adjusted by the concentration of the coating composition used for forming the corrosion-resistant film layer, the selection of the bar coater No. used for film formation, etc. The amount of the corrosion-resistant film layer can be measured by a known method such as X-ray fluorescence, an infrared film thickness meter, and weight measurement by film peeling.
[0064] 〈Hydrophilic membrane layer〉
[0065] The hydrophilic film layer is a film layer that imparts hydrophilicity to the surface of the fin material, and contains a conventionally known hydrophilic resin.
[0066] The hydrophilic resin may contain one type of resin or two or more types of resins as long as it has a hydrophilic group. Examples of the hydrophilic group include a hydroxyl group, a carboxyl group, a sulfonic acid group, and a polyether group.
[0067] Examples of the hydrophilic resin having a hydroxyl group include polyethylene glycol (PEG) and polyvinyl alcohol (PVA).
[0068] Examples of the hydrophilic resin having a carboxyl group include polyacrylic acid (PAA) and the like.
[0069] Examples of the hydrophilic resin having a hydroxyl group and a carboxyl group include carboxymethyl cellulose (CMC) and the like.
[0070] Examples of the hydrophilic resin having a sulfonic acid group include sulfoethyl acrylate and the like.
[0071] Examples of the hydrophilic resin having a polyether group include polyethylene glycol (PEG) and modified compounds thereof.
[0072] Among them, from the viewpoint that the desired hydrophilicity can be more appropriately exhibited even if a lubricating film layer is formed on the surface of the hydrophilic film layer, the hydrophilic resin is preferably one containing a sulfonic acid group, or preferably one containing a polyether group, i.e., an ether bond, more preferably one containing a sulfonic acid group and an ether bond, and particularly preferably an acrylic resin containing a sulfonic acid group and an ether bond.
[0073] The acrylic resin containing sulfonic acid and ether bond is an acrylic resin containing an unsaturated double bond group and a sulfonic acid group, and a representative example is 3-allyloxy-2-hydroxy-1-propanesulfonic acid sodium salt (HAPS), but other examples include acrylamidomethylpropanesulfonic acid, etc. In addition, the acrylic resin containing sulfonic acid and ether bond is not limited to these.
[0074] The hydrophilic resin may be a copolymer of two or more monomers having a hydrophilic group, in addition to the above. For example, a copolymer of acrylic acid and sulfoethyl acrylate may be used. The copolymer may be an alternating copolymer, a block copolymer, a graft copolymer, a random copolymer, etc. The arrangement of the monomers is not particularly limited.
[0075] The hydrophilic film layer preferably contains a surfactant in addition to the hydrophilic resin. Thus, when the lubricating film layer is formed on the hydrophilic film layer, the processability and good hydrophilicity brought by the lubricating film layer can be achieved. This can be considered to be the effect of the surfactant.
[0076] The surfactant may be any of anionic, cationic, and nonionic, but anionic surfactants are preferred from the viewpoint of being easily dispersed in the hydrophilic film layer. The surfactant may be used alone or in combination of two or more.
[0077] Examples of the anionic surfactant include polyoxyethylene alkyl ether phosphate (ポリオキシエチレンアルキルエーテルりん phosphate) and polyoxyethylene alkyl ether sulfide. Polyoxyethylene alkyl acid salt (Hydronate) Sulfosuccinate (Hydronate), etc.
[0078] Examples of the nonionic surfactant include ethylenediamine polyoxypropylene-polyoxyethylene condensate (Ethylenediamine polyoxypropylene-polyoxyethylene condensate)プロピレン-ポリオキシエチレン condensate), polyoxyethylene sorbitan monolaurate (ポリオキシエチレンソルビPolyoxyethylene polyoxypropylene block polymerックポリマー), polyoxyethylene sorbitan monostearate (ポリオキシエチレンソルビタンモノステアレート), etc.
[0079] The hydrophilic film layer may contain other optional components in addition to the hydrophilic resin and the surfactant within the range that does not impair the effects of the present invention. Examples of the optional components include various coating additives for improving the physical properties of the film layer.
[0080] Examples of coating additives include crosslinking agents, surface conditioners, wetting and dispersing agents, anti-settling agents, antioxidants, defoaming agents, rust inhibitors, antibacterial agents, and antifungal agents. These coating additives may be contained alone or in combination of two or more.
[0081] The film weight of the hydrophilic film layer of the present embodiment is preferably 0.1 to 28 mg / dm 2 Here, from the viewpoint of obtaining better hydrophilicity, the film weight of the hydrophilic film layer is preferably 0.1 mg / dm 2 More preferably 0.3 mg / dm 2 More preferably, 0.5 mg / dm 2 In addition, from the viewpoint of obtaining good coating operability when forming the hydrophilic film layer, and from the viewpoint of well exerting the functions of the corrosion-resistant film layer formed on the aluminum plate side of the hydrophilic film layer, the film amount of the hydrophilic film layer is preferably 28 mg / dm 2 Below, more preferably 25 mg / dm 2 the following.
[0082] The adhesion amount of the hydrophilic resin in the hydrophilic film layer is preferably 0.05 to 5 g / m 2 Here, from the viewpoint of obtaining sufficient hydrophilicity, the above-mentioned adhesion amount is preferably 0.05 g / m 2 More preferably 0.1 g / m 2 More preferably, 0.3 g / m 2 In addition, from the viewpoint of preventing the hydrophilic resin from dissolving out when the surface of the fin material is wetted with water and thus hindering the oil repellency of the functional film, the above-mentioned adhesion amount is preferably 5 g / m 2 Below, more preferably 1g / m 2 Below, more preferably 0.8 g / m2 the following.
[0083] When the hydrophilic film contains a surfactant, the amount of the surfactant attached to the hydrophilic film is preferably 0.0003 to 0.7 g / m 2 Here, from the viewpoint of obtaining sufficient hydrophilicity, the above-mentioned adhesion amount is preferably 0.0003 g / m 2 More preferably, 0.0005 g / m 2 More preferably, 0.001 g / m 2 In addition, when the hydrophilicity is too strong and there is a lubricating film layer on the hydrophilic film layer, the above-mentioned adhesion amount is preferably 0.7 g / m 2 Below, more preferably 0.5g / m 2 Below, more preferably 0.05 g / m 2 the following.
[0084] The amount of the hydrophilic film layer can be adjusted by the concentration of the coating composition for forming the hydrophilic film layer, the selection of the bar coater No., and the like.
[0085] 〈Lubricating film layer〉
[0086] The aluminum fin material of the present embodiment preferably further comprises a lubricating film layer on the surface of the hydrophilic film layer. More preferably, the lubricating film layer is the outermost layer of the aluminum fin material.
[0087] The lubricating film layer is a layer that improves the lubricity of the fin material surface, thereby reducing the friction coefficient of the fin material and improving the processability such as press formability when processing the fin material into fins.
[0088] The lubricating film layer of the present embodiment preferably contains a resin matrix and a hydrophilic component. Here, the so-called resin matrix means a resin component as a basic component that forms the lubricating film layer. With respect to the total amount of the components constituting the lubricating film layer, the content of the resin matrix is preferably 60% by mass or more. In addition, from the viewpoint of fully exerting the functions of the components other than the resin matrix, the above content is preferably 70% by mass or less.
[0089] The resin matrix of the present embodiment preferably contains polyethylene glycol (PEG) as a main component from the viewpoint of suppressing the decrease of the hydrophilic function due to heat and obtaining good heat resistance when combined with a specific hydrophilic component described later.
[0090] Here, the main component of the resin matrix means that the content thereof is 60% by mass or more based on the total amount of the resin constituting the resin matrix.
[0091] The above-mentioned polyethylene glycol also includes modified compounds thereof.
[0092] Examples of modified polyethylene glycol compounds include modified polyethylene glycols having a functional group in the structure, wherein the functional group has one or more bonds selected from the group consisting of a carbamate bond, an ester bond, and an ether bond. Among them, modified polyethylene glycols having a functional group having a carbamate bond in the structure are preferred because they have a functional group that is excellent in elongation.
[0093] When two or more polyethylene glycols having different molecular weights and structures are contained in the resin matrix, if the total amount thereof is 60% by mass or more, it can be said that the polyethylene glycol is contained as a main component.
[0094] In the resin matrix of this embodiment, the content of polyethylene glycol as the main component is preferably 60 mass % or more, more preferably 70 mass % or more, further preferably 80 mass % or more, and can also be 100 mass %, that is, the resin matrix is composed only of polyethylene glycol.
[0095] When the resin matrix of the present embodiment contains other resins other than polyethylene glycol, examples of the other resins include resins having a hydrophilic group, such as a hydroxyl group, a carboxyl group, a sulfonic acid group, and a polyether group.
[0096] Examples of the resin having a hydroxyl group other than polyethylene glycol (PEG) include polyvinyl alcohol (PVA) and the like.
[0097] Examples of the compound having a carboxyl group include polyacrylic acid (PAA) and the like.
[0098] Examples of the material having a hydroxyl group and a carboxyl group include carboxymethyl cellulose (CMC) and the like.
[0099] Examples of the compound having a sulfonic acid group include sulfoethyl acrylate and the like.
[0100] In addition, a copolymer of two or more monomers having a hydrophilic group can also be used.
[0101] The hydrophilic component of this embodiment is preferably a component containing at least one of a sulfonic acid group and an ester group, and more preferably the change in the amount of functional groups contributing to hydrophilicity before and after heating at 200° C. for 10 minutes is 15% or less. Thus, the hydrophilic effect of the hydrophilic film layer can be maintained without being lost due to heating, etc., and hydrophilicity with excellent heat resistance can be achieved.
[0102] Examples of the hydrophilic component containing at least one of a sulfonic acid group and an ester group include sulfonic acid acrylic compounds, phosphate compounds, acrylic compounds, etc. More preferably, the change in the amount of functional groups contributing to hydrophilicity before and after heating at 200° C. for 10 minutes is 15% or less.
[0103] The change in the amount of functional groups contributing to hydrophilicity of the hydrophilic component before and after heating at 200° C. for 10 minutes is preferably 15% or less, more preferably 10% or less, and even more preferably 5% or less.
[0104] In the present specification, the change in the amount of the functional group contributing to hydrophilicity can be measured using a Fourier transform infrared spectrometer.
[0105] In the present embodiment, the content of the hydrophilic component relative to 100 parts by mass of the resin matrix is preferably 2.0 to 6000 parts by mass. Here, from the viewpoint of obtaining high hydrophilicity, the above content is preferably 2.0 parts by mass or more, more preferably 5.0 parts by mass or more, further preferably 6.0 parts by mass or more, further preferably 8.0 parts by mass or more, and particularly preferably 10 parts by mass or more. On the other hand, from the viewpoint of obtaining good processability, the above content is preferably 6000 parts by mass or less, more preferably 5000 parts by mass or less, further preferably 4000 parts by mass or less, and particularly preferably 3000 parts by mass or less.
[0106] By making the content of the hydrophilic component in the resin matrix within an appropriate range, good processability and hydrophilicity related to splash prevention and reduction of ventilation resistance can be improved in a manner that does not interfere with each other.
[0107] The lubricating film layer of the present embodiment may contain other optional components in addition to the resin matrix and the hydrophilic component within the range not impairing the effects of the present invention. Examples of the optional components include various coating additives for improving the physical properties of the film layer.
[0108] Examples of coating additives include crosslinking agents, surfactants, surface conditioners, wetting and dispersing agents, anti-settling agents, antioxidants, defoamers, antifouling agents, rust inhibitors, antibacterial agents, and antifungal agents. These coating additives may be included alone or in combination of two or more.
[0109] The coating weight of the lubricating coating layer of the present embodiment is preferably 0.05 to 3.0 mg / dm 2 Here, from the viewpoint of obtaining sufficient corrosion resistance and heat-resistant hydrophilicity, the above-mentioned film amount is preferably 0.05 mg / dm 2 More preferably, 0.1 mg / dm 2 More preferably, 0.2 mg / dm 2 On the other hand, from the viewpoint of preventing a part of the components constituting the lubricating film layer from remaining on the surface when the surface of the fin material is wetted by water, thereby reducing the hydrophilicity, the above-mentioned film amount is preferably 3.0 mg / dm 2 Below, more preferably 1.5 mg / dm2 Below, more preferably 1.0 mg / dm 2 the following.
[0110] The amount of the lubricating film layer can be adjusted by the concentration of the coating composition for forming the lubricating film layer, the selection of the bar coater No., and the like.
[0111] In the aluminum fin material of the present embodiment, the total thickness of the corrosion-resistant film layer, the hydrophilic film layer, and the lubricating film layer is preferably 5 μm or less from the viewpoint of suppressing a decrease in heat exchange efficiency of the fin material.
[0112] 〈Aluminum Plate〉
[0113] The aluminum plate of the present embodiment is a concept including a plate made of aluminum and a plate made of an aluminum alloy, and an aluminum plate conventionally used for an aluminum fin material can be used.
[0114] As the aluminum plate, from the viewpoint of excellent thermal conductivity and workability, 1000 series aluminum specified in JIS H 4000: 2014 is preferred. More specifically, as the aluminum plate, aluminum with alloy numbers 1050, 1070, and 1200 is more preferred. However, the above description does not exclude the use of 2000 series to 9000 series aluminum alloys and other aluminum plates as the aluminum plate.
[0115] The aluminum plate can be appropriately made into a desired thickness according to the use and specifications of the fin material.
[0116] The fin material for heat exchangers preferably has a thickness of 0.08 to 0.3 mm. From the viewpoint of the strength of the fin, the thickness of the fin material is preferably 0.08 mm or more, and more preferably 0.1 mm or more. On the other hand, from the viewpoint of the processability of the fin and the heat exchange efficiency, the thickness of the fin material is preferably 0.3 mm or less, and more preferably 0.2 mm or less.
[0117] At least one surface of the aluminum plate has at least a corrosion-resistant film layer and a hydrophilic film layer in order, but it may also have at least a corrosion-resistant film layer and a hydrophilic film layer in order on both surfaces. In addition, when the corrosion-resistant film layer and the hydrophilic film layer are provided on both surfaces, the composition of each film layer on the two surfaces does not necessarily have to be the same.
[0118] 〈Base treatment layer〉
[0119] The aluminum fin material of the present embodiment may further include a base treatment layer between the aluminum plate and the corrosion-resistant film layer.
[0120] By providing the base treatment layer, the corrosion resistance of the aluminum plate can be improved, and the adhesion between the aluminum plate and the corrosion-resistant film layer can also be improved.
[0121] The base treatment layer of the present embodiment may be any layer that imparts corrosion resistance to the aluminum plate, and a conventionally known layer may be used, for example, a layer composed of an inorganic oxide or an inorganic-organic composite compound.
[0122] Examples of the inorganic material constituting the inorganic oxide and the inorganic-organic composite compound include chromium (Cr), zirconium (Zr), and titanium (Ti).
[0123] The layer composed of inorganic oxide as the base treatment layer can be formed by, for example, subjecting the aluminum plate to chromate phosphate treatment, zirconium phosphate treatment, zirconium oxide treatment, chromate chromate treatment, zinc phosphate treatment, titanate phosphate treatment, etc. However, the types of inorganic oxides are not limited to those formed by these treatments.
[0124] The layer composed of an inorganic-organic composite compound as a base treatment layer can be formed by, for example, subjecting an aluminum plate to a coating-type chromate treatment or a coating-type zirconium treatment. Specific examples of such an inorganic-organic composite compound include, for example, an acrylic-zirconium composite.
[0125] The film thickness of the base treatment layer is not particularly limited and may be appropriately set, but the film weight per unit area is preferably 1 to 100 mg / m2 in terms of metal (Cr, Zr, Ti). 2 The film thickness is preferably 1 to 100 nm.
[0126] The amount and thickness of the surface treatment layer can be adjusted by adjusting the concentration of the chemical conversion treatment solution used for forming the surface treatment layer and the film formation treatment time.
[0127] 〈Characteristics of aluminum fin materials〉
[0128] The aluminum fin material of the present embodiment has extremely excellent corrosion resistance.
[0129] If the aluminum fin material has low corrosion resistance, aluminum corrosion easily generates corrosion products, which are accompanied by a peculiar smell called corrosive odor.
[0130] Therefore, when no odor is detected at all or when only a slight odor is detected after the fin material is subjected to the moisture resistance test by the method described in Examples below, the corrosion resistance is evaluated to be very excellent.
[0131] Furthermore, when considering the use of aluminum fin materials in, for example, heat exchangers, it is necessary for the aluminum fin materials to have hydrophilicity equal to or higher than that of conventional materials.
[0132] Specifically, if the contact angle of the droplet measured by the method described in the examples below is 45° or less, it can be evaluated as having good hydrophilicity at or above the same level as before. The contact angle is more preferably 40° or less, further preferably 30° or less, and particularly preferably 20° or less.
[0133] 《Manufacturing method of aluminum fin material》
[0134] The aluminum fin material obtained by the manufacturing method of this embodiment comprises an aluminum plate, and a corrosion-resistant film layer and a hydrophilic film layer on at least one surface of the aluminum plate in this order. Furthermore, the manufacturing method comprises a step of applying and dehydrating a coating composition comprising an epoxy resin composition and at least one of silicon having an epoxy group and a silane coupling agent to form the corrosion-resistant film layer.
[0135] The fin material described in the above-mentioned "aluminum fin material" can be manufactured by the manufacturing method of this embodiment, but the fin material can also be manufactured by other manufacturing methods.
[0136] The manufacturing method of this embodiment is described in detail below. In addition, below, a base treatment layer, a corrosion-resistant film layer, a hydrophilic film layer and a lubricating film layer are formed in order on the surface of the aluminum plate, but the formation of the base treatment layer and the lubricating film layer is arbitrary. In addition, a film layer having other functions may also be provided.
[0137] When forming the base treatment layer on the surface of the aluminum plate, a conventionally known method can be used. Specifically, when the base treatment layer is a layer composed of an inorganic oxide, for example, the base treatment layer can be formed by subjecting the aluminum plate to chromate phosphate treatment, zirconium phosphate treatment, zirconium oxide treatment, chromate chromate treatment, zinc phosphate treatment, titanic acid phosphate treatment, etc.
[0138] When the surface treatment layer is a layer composed of an inorganic-organic composite compound, for example, the surface treatment layer can be formed by subjecting an aluminum plate to a coating type chromate treatment or a coating type zirconium treatment.
[0139] Before forming the surface treatment layer, the surface of the aluminum plate may be pre-degreased using an alkaline degreasing liquid. This improves the reactivity of the surface treatment and also improves the adhesion of the formed surface treatment layer.
[0140] Next, as a step of forming a corrosion-resistant film layer, a coating composition including an epoxy resin composition and at least one of silicon having an epoxy group and a silane coupling agent is applied and subjected to dehydration condensation.
[0141] By dehydration condensation, at least one of the silicon having an epoxy group and the silane coupling agent becomes silicone having an epoxy group, thereby forming a corrosion-resistant film layer including the epoxy resin and the silicone containing an epoxy group.
[0142] The coating composition may further contain an alcohol solvent, an ether solvent, the above-mentioned coating additive, etc., from the viewpoint of improving coating properties, workability, and physical properties of the film.
[0143] In the step of forming the corrosion-resistant film layer, after the above-mentioned dehydration condensation, drying may be performed as necessary.
[0144] The hydrophilic film layer can be formed by applying a coating composition containing a hydrophilic resin and, if necessary, a surfactant on the corrosion-resistant film layer and curing the composition by drying or the like.
[0145] The coating composition may further contain an aqueous solvent, a water-soluble organic solvent, the above-mentioned coating additive, etc., from the viewpoint of improving coating properties, workability, and physical properties of the film.
[0146] The lubricating film layer can be formed by applying a coating composition having a resin that improves lubricity, for example, a coating composition containing a resin matrix and a hydrophilic component, on the hydrophilic film layer and curing it by drying or the like.
[0147] From the viewpoint of improving coating properties, damage resistance, and physical properties of the film, the coating composition may further contain an aqueous solvent, a water-soluble organic solvent, or a conventional coating additive.
[0148] During the above curing, baking can also be performed.
[0149] The baking temperature is not particularly limited as long as the lubricating film layer is not peeled off, but is preferably 100 to 250° C., for example. Here, the temperature is preferably 100° C. or higher, more preferably 150° C. or higher. In addition, from the viewpoint of preventing oxidation of the resin in the lubricating film layer, the temperature is preferably 250° C. or lower, more preferably 200° C. or lower. The baking temperature is the oven temperature for baking.
[0150] The baking time is not particularly limited as long as the lubricating film layer does not peel off, but is preferably 3 to 30 seconds, for example. Here, it is preferred that the above time is 3 seconds or more, and more preferably 5 seconds or more. In addition, from the viewpoint of preventing oxidation of the resin of the lubricating film layer, the above time is preferably 30 seconds or less, and more preferably 20 seconds or less.
[0151] [Example]
[0152] The present invention will be described in more detail below with reference to Examples and Comparative Examples. However, the present invention is not limited to these Examples and may be modified and implemented within the scope consistent with the gist thereof, and all of these are included in the technical scope of the present invention.
[0153] 《Examples 1 to 13, Comparative Examples 1 to 19, Reference Example 1》
[0154] The aluminum plate was an aluminum plate having an individual thickness of 0.1 mm and conforming to alloy No. 1070 specified in JIS H 4000: 2014. A surface treatment layer was formed on one surface of the aluminum plate by chromate phosphate treatment.
[0155] Next, a coating composition was prepared by dispersing an epoxy resin composition (manufactured by DIC Corporation, EPICLON (registered trademark) 840) in water, and applied to the surface of the base treatment layer using a scraper coater according to the film amount shown in Table 1. After dehydration condensation was carried out at 200°C for 15 seconds, the coating composition was dried to form a corrosion-resistant film layer.
[0156] In the above coating composition, as a silicone precursor, a predetermined amount of epoxy-containing silicone emulsion was added in Examples 1 to 4 and Examples 11 to 13, a predetermined amount of epoxy-containing silicone A was added in Examples 5 and 6, a predetermined amount of epoxy-containing silicone B was added in Examples 7 and 8, a predetermined amount of epoxy-containing silane coupling agent was added in Examples 9 and 10, a predetermined amount of epoxy-free silicone A was added in Comparative Examples 3 and 4, and a predetermined amount of epoxy-free silicone B was added in Comparative Examples 5 and 6, so that the content of the obtained silicone became the value shown in Table 1 or 2. Here, the epoxy-containing silicone A and the epoxy-containing silicone B have different amounts of epoxy functional groups, and the amount of epoxy functional groups of the epoxy-containing silicone A is about 2 times more than that of the epoxy-containing silicone B per 1 mol. In addition, the functional groups of the epoxy-free silicone A and the silicone B are different, and the functional groups of the epoxy-free silicone A are about 2 times more than that of the epoxy-free silicone B per 1 mol.
[0157] In Comparative Example 1, Comparative Example 2, Comparative Examples 7 to 19, and Reference Example 1, silicon and a silane coupling agent were not added to the coating composition.
[0158] Next, a coating composition was prepared by dispersing an acrylic resin containing a sulfonic acid group and an ether bond in water, and the coating composition was prepared so that the coating weight was 3 mg / dm 2 The surface of the corrosion-resistant film layer was coated with a bar coater, dehydrated and condensed at 200° C. for 15 seconds, and then dried to form a hydrophilic film layer.
[0159] In the above-mentioned coating composition, a predetermined amount of epoxy-containing silicone emulsion was added in Comparative Examples 7 to 9, a predetermined amount of epoxy-containing silicone A was added in Comparative Examples 10 and 11, a predetermined amount of epoxy-containing silicone B was added in Comparative Examples 12 and 13, a predetermined amount of epoxy-containing silane coupling agent was added in Comparative Examples 14 and 15, a predetermined amount of epoxy-free silicone A was added in Comparative Examples 16 and 17, and a predetermined amount of epoxy-free silicone B was added in Comparative Examples 18 and 19, so that the content of the obtained silicone became the value shown in Table 1 or 2. Here, the epoxy-containing silicone A and the epoxy-containing silicone B have different amounts of epoxy functional groups, and the amount of epoxy functional groups of the epoxy-containing silicone A is about 2 times more than that of the epoxy-containing silicone B per 1 mol. In addition, the functional groups of the epoxy-free silicone A and the silicone B are different, and the functional groups of the epoxy-free silicone A are about 2 times more than that of the epoxy-free silicone B per 1 mol.
[0160] Finally, a coating composition was prepared by dispersing polyethylene glycol (manufactured by Sanyo Chemical Industries, Ltd., PEG6000) in water to obtain a coating with a film weight of 0.2 mg / dm 2 The lubricating film layer was formed by coating the surface of the hydrophilic film layer with a bar coater and baking at 150° C. for 15 seconds.
[0161] According to the above, an aluminum fin material is obtained.
[0162] "evaluate"
[0163] 〈Hydrophilicity〉
[0164] After immersing the fin material in a water tank filled with tap water for 8 hours, it was dried at 80°C for 16 hours. The above process was regarded as one cycle, and this immersion and drying were repeated for 5 cycles. After returning to room temperature, about 2 μL of ion exchange water was dripped on the surface of the fin material, and the contact angle of the droplet was measured using a contact angle meter (manufactured by Kyowa Interface Science Co., Ltd.: CA-05 model). The contact angle was measured 3 times for each sample, and the average value was taken as the contact angle.
[0165] The results show that in the "hydrophilicity" of Table 1, if the contact angle is 45° or less, it can be evaluated as having good hydrophilicity at or above the same level as before, and more preferably the contact angle is 40° or less, and the smaller the contact angle, the higher the hydrophilicity.
[0166] 〈Corrosion resistance〉
[0167] The moisture resistance test was performed by leaving the fin material in an atmosphere of 40° C. and a humidity of 98% RH or more for 500 hours.
[0168] The fin material was evaluated for odor intensity 300 hours and 500 hours after the start of the moisture resistance test. The evaluation criteria are as follows: if the evaluation is 0 to 2 after 300 hours and 500 hours after the start of the moisture resistance test, it can be judged that the corrosion resistance is very good. The results are shown in "Corrosion Resistance" in Table 1.
[0169] 0: No smell at all.
[0170] 1: Although a slight odor is detected, it is impossible to tell what the odor is (detection threshold).
[0171] 2: Sense faint odors and be able to determine what the odor is (cognitive threshold).
[0172] 3: The smell is strong and you can easily tell what it is.
[0173] 4: The smell is very strong and the type of smell is unpleasant.
[0174]
Table 1
[0175]
[0176]
Table 2
[0177]
[0178] From the results of Tables 1 and 2, it is understood that by including epoxy-containing silicone in the corrosion-resistant film layer, extremely excellent corrosion resistance can be achieved.
[0179] On the other hand, as shown in the results of Comparative Examples 3 to 6, even if silicone is included in the corrosion-resistant film layer and the silicone does not contain an epoxy group, only the same level of corrosion resistance as in Comparative Example 1 can be achieved. Simply including silicone in the corrosion-resistant film layer cannot improve the corrosion resistance.
[0180] Furthermore, according to the results of Comparative Examples 7 to 15, the epoxy-containing silicone is not contained in the corrosion-resistant film layer but is contained in the hydrophilic film layer, and no improvement in corrosion resistance is observed. In addition, the hydrophilic effect of the hydrophilic film layer is impaired.
[0181] In addition, as shown in Table 2, when the corrosion-resistant film layer does not include silicone containing epoxy groups, as shown in Reference Example 1, if the film thickness is not increased to 25 mg / dm 2 In contrast, the corrosion-resistant film layer including epoxy-containing silicone can achieve equivalent corrosion resistance with a small film amount.
[0182] As described above, the corrosion-resistant film layer of the present embodiment has extremely excellent corrosion resistance, so the film amount can be reduced, which is also advantageous from the viewpoint of production cost.
Claims
1. An aluminum fin material comprising, in order, an aluminum plate, and a corrosion-resistant film layer and a hydrophilic film layer on at least one surface of the aluminum plate, The corrosion-resistant film layer includes an epoxy resin and silicone containing an epoxy group.
2. The aluminum fin material according to claim 1, wherein: The content of the epoxy-containing silicone in the corrosion-resistant film layer is 0.1 to 20% by mass.
3. The aluminum fin material according to claim 1 or 2, wherein: The amount of the corrosion-resistant film layer is 0.1 to 20 mg / dm 2 .
4. The aluminum fin material according to claim 1 or 2, wherein: The hydrophilic film layer includes an acrylic resin containing a sulfonic acid group and an ether bond.
5. The aluminum fin material according to claim 1 or 2, wherein: A lubricating film layer is further provided on the surface of the hydrophilic film layer.
6. The aluminum fin material according to claim 5, wherein: The lubricating film layer comprises: A resin matrix containing polyethylene glycol as a main component; A hydrophilic component containing at least one of a sulfonic acid group and an ester group.
7. The aluminum fin material according to claim 1 or 2, wherein: A surface treatment layer is further provided between the aluminum plate and the corrosion-resistant film layer.
8. A method for manufacturing an aluminum fin material, comprising an aluminum plate, and a corrosion-resistant film layer and a hydrophilic film layer on at least one surface of the aluminum plate in order, wherein: The method comprises the steps of applying a coating composition containing an epoxy resin composition and at least one of silicon having an epoxy group and a silane coupling agent and subjecting the coating composition to dehydration condensation to form the corrosion-resistant film layer.
Citation Information
Patent Citations
Aluminum fin material
JP2021162164A
Aluminum fin material
JP2021162165A
Aluminum fin material
JP2022161706A